Analisis Implementasi Pendekatan Saintifik dalam Meningkatkan Keterampilan Proses Sains Anak Usia Dini - Ni Luh Putu Nina Sriwarthini; Ika Rachmayani; Filsa Era Sativa (Jurnal Pendidikan dan Konseling (JPDK), 2022)
The 2013 PAUD curriculum stipulates a scientific approach as a characteristic of the national PAUD curriculum. This means that early childhood learning should apply a scientific approach in every learning meeting. In practice, kindergarten / PAUD schools still have not optimized this, especially during the Covid-19 pandemic. This study uses a qualitative descriptive research approach. The research instrument used for data collection was the lesson plan implementation at two participating schools, supplemented by supporting data in the form of observation notes. The data that has been collected in this study include: First, data on the learning process carried out in the classroom to collect potential problems that exist in learning activities. This data was obtained from lesson plans, video recordings of learning implementation and observation activities carried out by researchers. Second, the results of interview transcripts were conducted after the observation took place. This data is used by researchers to purchase problems that teachers and schools have regarding their science performance in the learning activities that have been carried out. The results showed that the implementation of the scientific approach in both Kindergartens was still relatively low, in terms of the emergence of science process skills, which on average were below 3. The main obstacle to the low implementation of the scientific approach in both Kindergartens was because of the lack of training for teachers to develop varied and based learning activities. scientific.